The Iberian dictatorships and agricultural modernisation after Second World War - Freire, Dulce (2016)
Where the relationship between the state and agriculture is concerned, the three decades that followed World War II in Europe proved to be especially significant. Two dominant historical processes can be identified: the consolidation of the democratic model of the welfare state and the rapid modernization of the agrarian sector. As Portugal and Spain were ruled between the 1930s and the mid-1970s by fascist dictatorships - the New State in Portugal (1933-1974) and Francoism in Spain (1939- 1975) - they clearly did not conform to the constitutional arrangements of liberal democracy. But to what extent did Portugal and Spain under fascism embrace the rapid modernization of the agrarian sector? This is the issue addressed in this chapter.